Recent advances in the aetiology of recurrent aphthous stomatitis (RAS). Issue 1155 (11th February 2021) - Wang, Zihan; Cao, Haibo; Xiong, Jianqi; Lu, Yilong; Deng, Yixiao; Nan, Han; Zheng, Shutian; Ye, Hui; Cao, Zhensheng
Abstract: Recurrent aphthous stomatitis (RAS) is the most common disease of oral mucosa, which almost attacks each individual once in their lifespan. Although plenty of factors have been suggested to play a role in the pathogenesis of RAS, the aetiology of RAS is still controversial, which might lead to limited clinical therapies in accordance with each RAS patient. This review mainly illustrates recent advances in potential causes associated with RAS in detail. Deeper comprehension of the aetiology of RAS will support doctors and researchers to make a better management of RAS patients and to discover new treatments. The aetiology of RAS is complicated, hence we should take a comprehensive view into its aetiology, with multiple potential factors being considered. Sample collection of RAS patients have greatly limited the progress in the aetiology of RAS. A research model of multiagency cooperation can help achieve perfect sample collection of year-round and multiposition.